2011
DOI: 10.1002/stem.574
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Human Mesenchymal Stem Cells with Pioglitazone Improved Efficiency of Cardiomyogenic Transdifferentiation and Cardiac Function

Abstract: The efficacy of transplantation of default human marrowderived mesenchymal stem cells (MSCs) was modest. In this study, our challenge was to improve the efficacy of MSC transplantation in vivo by pretreatment of MSCs with pioglitazone. MSCs were cultured with or without medium containing 1 lM of pioglitazone before cardiomyogenic induction. After cardiomyogenic induction in vitro, cardiomyogenic transdifferentiation efficiency (CTE) was calculated by immunocytochemistry using anti-cardiac troponin-I antibody. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…Recent evidences suggested that exposure to exogenous hydrogen peroxide (H 2 O 2 ) could increase ROS formation in ADSCs and attenuated cell adhesion, whereas the use of ROS scavengers, such as antioxidant, can reverse the impaired adhesion mediated by integrin [9], [10]. Previously, several approaches have been developed to enhance transplanted cell survival in ischemic myocardium through increasing their adhesive ability, including pretreatment before transplantation and genetically engineering [11], [12], [13]. For example, Laflamme et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidences suggested that exposure to exogenous hydrogen peroxide (H 2 O 2 ) could increase ROS formation in ADSCs and attenuated cell adhesion, whereas the use of ROS scavengers, such as antioxidant, can reverse the impaired adhesion mediated by integrin [9], [10]. Previously, several approaches have been developed to enhance transplanted cell survival in ischemic myocardium through increasing their adhesive ability, including pretreatment before transplantation and genetically engineering [11], [12], [13]. For example, Laflamme et al .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyogenic differentiation of BM-MSC has been reported in both allogeneic 22,28 and xenograft models. 29,30 Toma et al found that human BM-MSC injected into healthy SCID/beige adult mice hearts underwent cardiomyogenic differentiation. 29 In vitro studies suggest that a cell-to-cell direct contact between resident cells and BM-MSC is critical in MSC differentiation into cardiomyocytes or smooth muscle cells.…”
mentioning
confidence: 99%
“…However, surviving MSCderived cardiomyocytes were rare, suggesting that these improvements in cardiac function may be caused by factors secreted from the transplanted cells, which could produce antiapoptotic effects or inhibit post left ventricular remodeling after MI. 64 A most interesting finding from the study was that oral pioglitazone treatment significantly increased the number of surviving, transplanted cells and blood vessel formation in the infarction zone. Although the precise mechanism of orally delivered pioglitazone on transplanted MSC-derived cardiomyocytes was unknown, and cardiac parameters were not improved compared to transplantation with MSC-derived cardiomyocytes alone, this study does show the potential for small molecule methods to enhance tissue-specific stem cell transplantation into cardiomyocytes and influence the cardiac cellular environment post-MI.…”
Section: That Enhance the Production Of New Cardiac Cells Or Facilitamentioning
confidence: 97%